Theoretical Study on Storage and Release of Firefly Luciferin - Guo, Ya‐Jie; Cui, Cheng‐Xing; Liu, Ya‐Jun (Photochemistry and photobiology, 2022)
Among numerous bioluminescent organisms, firefly is the most studied one. Recent experiment proposed that sulfoluciferin (SLH2) may serve as a storage form of luciferin (LH2). In the present article, we employed density functional theory calculation to uncover the mechanism and detailed process of the storage and release reactions. Due to lack of available crystallographic structure of the related enzyme, the calculation was performed on a model system. For the storage reaction, possible amino acid residues were used for imitating the protein environment. For the release reaction, the dielectric constant of 3.0 was employed to simulate the polarity of the protein cavity. The computational results indicated that the reactions from LH2 to SLH2 and from SLH2 to LH2 are both exergonic, which favor the storage and release processes and coincide with the experimental observation. Basing on experimental and current theoretical study, we supplemented the stages of LH2 storage and release in the entire bioluminescent cycle of firefly. The current theoretical calculation could inspire the study on LH2 storage and release of other bioluminescent organisms. This figure shows an entire bioluminescent cycle of firefly by supplementing the stages of LH2 storage and release in the present paper.